Le cinéma est-il bachelardien? hypothèse théoriques autour de la matière (et) des images (Altre Modernità, 2012)
Either in his epistemological or "poetic" writings, Gaston Bachelard has almost never referred to the cinema – of which he was contemporary –, unlike other artistic practices, more valued, such as painting or engraving. Where, exceptionally, he mentions the device that produces moving images, this is called as a foil or a negative model, also like his theoretical "opponent" Henri Bergson. This text offers from this "missed encounter" between Bachelard and films to re-examine the relation of the philosopher with the material, either in the books on the four elements and in the epistemological works like Le matérialisme rationnel and Les intuitions atomistiques. Indeed, cinema is an ambiguous art: deeply material in its main relationship with the real and, at the same time, secured by its mode of production (recording) and presentification (projection) of the images, an immaterial dimension that is now accelerating. By his constant attention to the tangible presence of things, to the qualities of material, to the fundamental relationship between the eye and the hand in a perspective even more phenomenological, Bachelard's thinking help to think the material dimension of motion pictures, often underestimated or simply removed. Conversely, the cinema has been accustomed us to original forms of perception (the blur, the fade, the overprinting, the slow or accelerated motion), which can explain certain aspect of philosopher’s thinking, which have been very few convened.
Keywords: Cinema; Bergson; Perception; Mouvement Image